Improving Student Learning Activities in Islamic Education Learning Using the Modeling The Way Learning Strategy at SD Negeri 11 Bandar Dua - Nurjannah; Suraiya Fitri (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve students' learning activities in carrying out prayer worship through the application of the Modeling The Way learning strategy to grade III students of SDN 11 Bandar Dua in the 2023/2024 Academic Year. This study is a classroom action research that uses four steps, namely planning, action, observation, and reflection. The subjects of this study were 21 grade III students of SDN 11 Bandar Dua. The data for this study were obtained using test and observation techniques. Tests are used to measure students' learning outcomes in understanding and carrying out prayer worship, while observations are used to analyze students' learning activities and teacher involvement in the learning process. The data analysis techniques used in this study are qualitative and quantitative descriptive analysis by comparing the results of tests and observations in the initial conditions, cycle I, and cycle II. The results showed that the application of the Modeling The Way learning strategy significantly increased students' learning activities and their understanding in carrying out prayer worship. There was an increase in students' test scores and their involvement in the learning process from cycle I to cycle II. Thus, the use of the Modeling The Way learning strategy can be used as an effective method in improving the understanding and practice of prayer worship in elementary school students.